Removal of Cr(Ⅵ) from tannery biochemical tail water by chitosan modified hydrothermal carbon - WANG Sen; WANG Ying; ZHANG Yuanru; LI Chen; DONG Zhikui; CHEN Wenhui; SUN Fule; JI Renjie (Gongye shui chuli)
The hydrothermal carbon precursor(WBC) was prepared by hydrothermal carbon method and modified with chitosan to obtain the modified hydrothermal carbon(CWBC). The materials were characterized by SEM, FT-IR, and nano-particle size surface potential analyzer, and the adsorption characteristics and adsorption mechanism of CWBC for Cr(Ⅵ) in wastewater were investigated. The results showed that CWBC had a rough surface and compact three-dimensional network structure, and there were functional groups such as C—N/N—H, C—H and C—O on the surface. Most of the pores in CWBC was mesoporous, while a small part was macroporous. It was a typical mixed structure, which enhanced its adsorption performance for Cr(Ⅵ). When the dosage of CWBC was 1.0 g/L, the solution pH was 3, the initial mass concentration of Cr(Ⅵ) was 10 mg/L, and the reaction temperature was 35 ℃, the adsorption capacity of Cr(Ⅵ) in simulated wastewater by CWBC was higher than 9.9 mg/g, and the removal rate of Cr(Ⅵ) was up to 99%. In addition, the removal rate of Cr(Ⅵ) in the biochemical tail water of actual tannery could also reach 73.33%. The regeneration results showed that the removal rate of Cr(Ⅵ) still reached more than 75% after 8 adsorption-desorption cycles, indicating that the composite material had good recycling performance. The adsorption process of Cr(Ⅵ) by CWBC conformed to the quasi-first-order kinetics and Langmuir model, which was a monolayer adsorption, and dominated by physical adsorption. The thermodynamic analysis results showed that the adsorption of Cr(Ⅵ) by CWBC was an active endothermic reaction.